Sensory mapping using High-Resolution 7 T fMRI - Asghar, Michael (2019)
One of the aims of medical physics and neuroscientific research is to noninvasively measure primary sensory human brain function with high spatial and temporal resolution. Imaging modalities such as functional magnetic resonance imaging (fMRI) have allowed a better understanding of broad neuronal properties. The Chapters in this thesis focus on high spatial resolution mapping in the visual and somatosensory system using ultra-high field (7 T) fMRI.